Out-of-Season Epidemic of Respiratory Syncytial Virus during the COVID-19 Pandemic: The High Burden of Child Hospitalization in an Academic Hospital in Southern Italy in 2021 - Daniela Loconsole; Francesca Centrone; Caterina Rizzo; Désirée Caselli; Azzurra Orlandi; Fabio Cardinale; Cristina Serio; Paola Giordano; Giuseppe Lassandro; Leonardo Milella; Maria Teresa Ficarella; Maria Elisabetta Baldassarre; et al. (MDPI AG, 2022)
Respiratory syncytial virus (RSV) infection is the most common cause of hospitalization in young children. In the last 2 years, public health measures aimed at controlling the spread of SARS-CoV-2 have affected the epidemiology and seasonality of RSV worldwide. The aim of this descriptive retrospective observational study was to describe the characteristics of children hospitalized with RSV in an academic tertiary care hospital in Southern Italy in 2021. We also investigate the seasonal trends of RSV from 2017 to 2021. The demographic characteristics, comorbidities, clinical data, and coinfections were retrospectively evaluated. Compared with previous seasons, the 2021 outbreak of RSV was characterized by an increased number of patients, with a delayed peak observed in November. Overall, 179 children, including 128 (71.5%) aged <12 months, were hospitalized for RSV infection between August and December 2021. Ten children (5.6%) were admitted to the intensive care unit (ICU), all aged <5 months. One patient (0.5%) aged <1 month with severe comorbidities died. The severity of symptoms was significantly associated with younger age, underlying chronic disease, and the length of hospital stay (p < 0.05 each). History of prematurity was not significantly associated with the presence of coinfections. Because of the high burden of RSV infection and the expected larger RSV epidemics resulting from a greater number of RSV-naïve children, systematic epidemiological and virological surveillance is needed. Appropriate pathways for access to RSV prevention in all infants should also be introduced.